The «Ethnie» and the «Imaginative Geographies» of the State of Israel: The policy that reveals a creeping annexation of the Palestinian land - Δόμπα, Ελένη (Πανεπιστήμιο Πελοποννήσου, 2016)
The conflict between Israelis and Palestinians has multiple dimensions. Following a certain policy, the Israelis are trying to lead the Palestinians to flee and to annex their land in the state of Israel. The annexation of these territories is necessary for Israelis to enable them to maintain their identity as a nation. Alongside the settlements and the barrier, Israelis have created a broader expansionary policy based on movements that emphasize other features that highlight the status of their nation as an ethnie. This policy is based on the framework of an imaginary geography which characterizes the cultural and historical construct they have created around the relationship of the nation with the land of Palestine and codes and rules of Orientalism to establish the pretext of “security”. The present study focuses on these data on the basis of the views of Anthony Smith for the Ethnie and of Edward Said on Orientalism and Imaginative Geographies.
Η «Εθνότητα» και οι «Φαντασιακές Γεωγραφίες» του Κράτους του Ισραήλ: Η πολιτική που αποκαλύπτει μια υφέρπουσα προσάρτηση της Παλαιστινιακής γης
Keywords: Αραβο-Ισραηλινή Σύγκρουση; Ισραήλ--Πολιτική και διακυβέρνηση; Ισραήλ--Σχέσεις--Παλαιστίνη; Οριενταλισμός; Εθνότητες; Φαντασιακές Γεωγραφίες; Σιωνισμός; Μετανάστευση; Πολιτική του Ισραήλ